Antibacterial Biomaterials: Nonleaching Antibacterial Concept Demonstrated by In Situ Construction of 2D Nanoflakes on Magnesium (Adv. Sci. 1/2020). Issue 1 (8th January 2020) - Wang, Guomin; Jiang, Wenjuan; Mo, Shi; Xie, Lingxia; Liao, Qing; Hu, Liangsheng; Ruan, Qingdong; Tang, Kaiwei; Mehrjou, Babak; Liu, Mengting; Tong, Liping; Wang, Huaiyu; et al.
Abstract : In article number 1902089, Huaiyu Wang, Jie Zhuang, Guosong Wu, Paul K. Chu, and co‐workers demonstrate a non‐leaching antibacterial concept on nanoflakes. The nanoflakes stretch bacteria on contact and the mechanical stress imposed triggers a series of reactions such as membrane rupture and reactive oxygen species burst leading to bacteria death. Biomaterials with the non‐leaching antibacterial ability are very promising in implants and cause little side effects and inflammation in vivo.